Study of Land Cover Change in the Mangrove Ecosystem of the East Coast of Surabaya - Syamsu, Imam Fauzi; Nugraha, Ahmad Zaky; Nugraheni, Claudia Tyas; Wahwakhi, Salmana (Media Konservasi, 2018)
The East Coast of Surabaya (Pamurbaya) is a coastal area in Surabaya City that has mangrove ecosystem and it has been designated as a protected area based on Surabaya District Regulation No. 12 of 2014. However, the existence of mangrove in the area is threatened by land use changes. This research aims to investigate the changes of mangrove distribution, extent and canopy density in Pamurbaya. Unsupervised classification and determination of NDVI values are used to discover changes in mangrove ecosystems in the period of 2000 and 2015. The results of this research showeds that mangrove spreading pattern in the period of 2000 until 2015 has shift towards the sea as it is pressed by the development of Surabaya City that leads to the east (coast). In general, the mangrove ecosystem in Pamurbaya over a period of 15 years has increased by 67 ha. The mangrove vegetation density level also increased to high density level with the value of NDVI between 0.81-1.00. Mulyorejo is a subdistrict with the greatest increase of mangrove area and density than the other 6 subdistrict in Pamurbaya. Keyword: Mangrove, NDVI, pamurbaya, unsupervised classification